Diagnosis of aviation electric commutator motors in operating condition - Курилов, В. И. (Proceedings of National Aviation University (archive), 2000)
Considered are the aspects of using monitoring systems based on application of information parameters commutation process in brush collector of aviation electric motors in the process of operation